8 Knowledge translation in the digital world: using wikipedia as an EBM teaching platform. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Murray, Heather; Dawson, Jennifer; Walker, Melanie; Maggio, Lauren
Abstract : Objectives: Learning outcomes for participants: Understand structure of Wikipedia pages and process for editing and adding citations. Examine Wikipedia–based assignments used in two different medical schools for different learner populations (pre–clerkship and clerkship students). Identify barriers and supports that would enhance feasibility for adoption in participant environments and for targeted groups of learners. Plan student assessment that evaluates both EBM whole task capability and critical thinking for a variety of learner types and level. Method: Background: With more than 220M page views per day, Wikipedia is the ultimate knowledge translation platform, providing unbiased, structured and rigorously-sourced medical information free to the world. Based on the instructors' experience teaching Wikipedia editing courses to medical students at Queen's University and the University of California, San Francisco (UCSF), editing Wikipedia pages allows learners to improve Wikipedia, improve communication skills, and build critical appraisal skills while practicing Evidence-Based Medicine (EBM). Participants in this workshop will learn how to design and implement Wikipedia-based EBM exercises for a broad range of learner types and training levels. Results: Resources: Participants will need to bring laptops or tablets for hands-on activities within Wikipedia. Instructors will distribute assignment and assessment materials from the Wikipedia-based longitudinal EBM exercises at Queen's University and at UCSF. We will actively collaborate to scale these resources to ensure suitability for learners across the continuum of medical education. Finally, we will troubleshoot potential challenges and brainstorm solutions for regional implementation of these exercises. Conclusions: N/A.